Japan as Location of Foreign Direct Investment (FDI) - Barriers and Recommendations - Bobowski, Sebastian (Japonia jako lokalizacja bezpośrednich inwestycji zagranicznych - bariery i rekomendacje, 2010)
The third largest economy have been losing its position in global economic system because of years of neglect that had generated administrative, cost and cultural barriers for trade and investment flows. Far from potential of Japanese economy FDI inflows indicate the necessity of reform in order to increase competitiveness of the economy. Recommendations include improvements of M&As, FDI regulations, sectoral strategies, reduction of business costs, increase of system transparency, revitalisation using foreign capital. In particular, investors expect reduction of tax rate and labour costs. In this context, foundations of government strategy should be more ambitious.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 284-293
Keywords: Japan; Foreign Direct Investment; mergers & acquisitions